Estrategias preventivas para disminuir la mortalidad materna por intervención de parteras en la comunidad Puerto Ecuador provincia de Sucumbíos - Jimenez Delgado, Yuli Fernanda (2018)
The present study was conducted in the Community of Puerto Sucumbios, with the objective of implementing educational and practical strategies, through the implementation and advice on the importance of the assistance of prenatal check-ups and maternal complications for intra-domiciliary deliveries. people of said community in order to contribute to the improvement of the application of this and to provide education and achieve awareness to pregnant women. A descriptive, quali - quantitative and field study was carried out using surveys and observation techniques to identify the practical level of knowledge that the population has about the work carried out by the midwives and their complications. lt was evidenced that 57% of the population was unaware of the complications involved in the intervention of a midwife and 43% knew, so it was necessary to implement an increase in home visits, and prenatal check-ups, which is achieved with the early recruitment of pregnant women; Regarding gynecological complications, itis clear that 64% know what are the complications that prevent with prenatal check-ups, 36% do not know this is why after the application of the proposed strategies 100% was achieved of the study sample known about maternal deaths by intervention of midwives, while 89% can already identify the interventions to perform in the face of a maternal alarm, in order to contribute to the reduction of maternal complications thus improving the quality of life maternal